Pengaruh Penerapan Metode Pembelajaran Tipe Card Sort Terhadap Minat Belajar Pendidikan Agama Kristen Siswa Kelas IX SMP Negeri 2 Sirandorung Kabupaten Tapanuli Tengah Tahun Pembelajaran 2023/2024 - Darliana Juni Manurung; Maria Widiastuti; Helena Turnip; Andrianus Nababan (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
This research aims to determine the positive and significant influence of the application of the Card Sort type learning method on the interest in studying Christian Religious Education of Class IX Students of SMP Negeri 2 Sirandorung, Central Tapanuli Regency for the 2023/2024 Academic Year. This research uses a quantitative pre-experimental design method in the form of a One Shot Case Study. The population of this study was all students of IX SMP Negeri 2 Sirandorung, totaling 114 people in 3 study class groups. Sampling was taken using a purposive sampling technique, namely class IX-1, totaling 38 people. Data was collected using a questionnaire with 35 items. 17 items for the questionnaire for variable This is proven by the results of the positive relationship test calculation, the value of rxy = 0.487 > rtable (α=0.05; IK=95%; n=38) = 0.320, thus it is known that there is a positive relationship between variables X and Y .Testing a significant relationship, the value obtained is tcount = 4.078> ttable (α=0.05;dk=n-2=36)= 2.028, thus there is a significant relationship between variables X and Y. Testing the regression equation, we get the regression equation Y ̂ =